Inferências sobre a preferência alimentar e a influência vitamínica na dieta de morcegos nectarívoros. - Torezani, Paulo Rogério (2018)
The relation between plants and pollinating bats is well known among the literature. The pollinating bats of the Neotropical region belong to the Phyllostomidae family which includes frugivorous bats (e.g., Subfamily Stenodermatinae) and nectarivores (e.g., Glossophaginae Subfamily). In Brazil, 74 species of these bats are present. The diversity in the chemical composition of flowers and fruits related to nectarivore and frugivorous groups is illustrated by the variation of the different amounts of sugars found in their pulps and nectars. This relationship between the preference of the pollinators / dispersers and the variation of the composition / concentration of sugars has inspired several works related to the theme. Most of these studies were based on the hypothesis that New World bats prefer the nectar sugars and fruits they normally ingest in the natural environment. Most of the studies suggested that new studies are needed to find possible nutritional factors associated with nectar, as well as the composition / concentration of sugars. Based on this assumption, the objective of this study was to evaluate the alimentary preference of nectarivorous bats for sugary solutions with different compositions / concentrations and addition of vitamins. For this, the type of sugar preferred by nectarivorous bats was tested; the preferred sugar concentration by nectarivorous bats and the addition of vitamins to determine if this influences or alters the feeding preference of nectarivorous bats. The methodology used involved food preference tests using artificial drinkers, which were subdivided into three stages: composition of sugars (sucrose, fructose and glucose), concentration of sugars (low, medium and high) and addition of vitamins (vitamin C and vitamin B12). Differences in dietary preference over the types of solutions were inferred from the number of visits of bats in each drinking fountain as well as the analysis of the amount of solution ingested. This study was carried out in the Forest Park of the National Institute of the Atlantic Forest (Santa Teresa-ES). The results of this study conclude that nectarivorous bats develop a preferential behavior for sugar sucrose, to the detriment of monosaccharides such as fructose and glucose (hexoses), which refutes 10 the hypothesis that they even prefer sugar normally found in floral nectar. In relation to the concentration, it was observed that, as expected and pointed out by other studies, the preferred optimum concentration is found in floral nectar (20%), however, alternatively, larger and smaller concentrations can be ingested. Regarding preference based on the presence / absence of vitamins, it was found that chiroptera prefer solutions of nectars containing these types of micronutrients, suggesting that they are able to identify them during foraging.